Discovery of crinoid stem fragment imprints on the epitheca of rugose corals - V. N. Komarov; Ya. D. Grechishnikova (Известия высших учебных заведений: Геология и разведка, 2025)
Background. Paleoecology, which studies the reconstruction of ecosystems of the geological past and their temporal development, has occupied a key place in the complex of geological sciences. Theoretical and applied geology are increasingly incorporating the results of paleoecological analysis, primarily for facies analysis, paleogeography, and detailed stratigraphy.Aim. To study the first discovered imprints of crinoid stem fragments on the epitheca of rugose corals and elucidate their paleoecological significance.Materials and methods. More than 2300 corallites were macroscopically examined. The detected imprints of crinoid stem segments were studied using a binocular microscope MBS-1.Results. A new form of preservation of crinoids has been established, represented by their segment imprints on the epitheca of rugose corals.Conclusion. The revealed mechanism of formation of crinoids segment imprints on the epitheca of rugose corals indicates a calm hydrodynamic environment and allows us to confidently determine the position of the corallite on the ground.